دور حوكمة الشركات في تحسين الأداء المالي دراسة ميدانية لعينة من المصارف العاملة بولاية سنار - د. أحمد يوسف مولود إسماعيل; أ. رانية حمدون الجزولي، باحثة . (White Nile Journal for Studies and Research, 2025)
The study examined the role of corporate governance in improving financial performance, and aimed to know the effect of the rule of fair and equal treatment, disclosure and transparency in improving financial performance, and tested the hypotheses: There is a statistically significant relationship between (applying the rule of fair and equal treatment and the rule of disclosure and transparency) and improving financial performance. The SPSS program was used for statistical analysis and processing, and the results were reached: The corporate governance framework guarantees equal treatment for all shareholders, which helps in effective financial performance. Disclosing tangible risk factors in the foreseeable future contributes to controlling financial performance. The study recommended providing all shareholders with the opportunity to obtain To effectively prevent violations of their rights, disclose the remuneration of the Board of Directors and senior managers, their salaries, incentives, and how they are appointed Keywords: Gouvernance, Corporate gouvernance, Financial performance.